2020
DOI: 10.3390/ijerph17228427
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multiple Exposures and Ad-Skipping Behavior on Recall of Health Messages on YouTubeTM

Abstract: Although measuring exposure to public health messages is key to understanding campaign effectiveness, little is known about how exposure to and avoidance of digital ad messages may influence self-reported ad recall. A sample of 15–24-year-olds (n = 297) received a varying number of forced-view and skippable test ads across multiple simulated YouTubeTM sessions. Each session was coded for whether the participant viewed the ad or skipped it. While a majority of participants recalled the test ad, the odds of ad r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…An effective advertising campaign contributes to the notoriety of a product, service or cause, and can arouse the interest of the recipient and lead them to perform a certain action (Sigit, 2018). In this sense, a campaign can influence attitudes and behaviors (Gracia et al , 2018; Romberg et al , 2020).…”
Section: Domestic Violence Awareness Campaigns and Their Effectivenessmentioning
confidence: 99%
“…An effective advertising campaign contributes to the notoriety of a product, service or cause, and can arouse the interest of the recipient and lead them to perform a certain action (Sigit, 2018). In this sense, a campaign can influence attitudes and behaviors (Gracia et al , 2018; Romberg et al , 2020).…”
Section: Domestic Violence Awareness Campaigns and Their Effectivenessmentioning
confidence: 99%
“…In digital media, advertising is often skippable and perceived as more of a disturbance [8,9], and the obstacles of data privacy make it complicated to obtain or create metrics that are standardized across platforms and parsimonious. There is little research on exposure of media campaigns in a real-life digital setting, likely owing to limited options of viable platforms [10,11]. An increasing number of studies are being conducted within social media, specifically Facebook, to recruit participants [12][13][14], as well as to assess the feasibility of using Facebook to reach and survey youths and young adults about the use of tobacco and other substances [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…There is only one study utilizing an experimental design to assess individual-level digital campaign ad exposure and individual outcomes. In a lab-based setting, Romberg et al 42 randomized participants to increasing levels of exposure to a mix of forced and skippable digital video ads for e-cigarette use prevention in a naturalistic online browsing environment. The authors found that ad recognition did not vary in a dose-response manner by randomized exposure levels when participants were able to skip ads but ad recognition was sensitive to non-randomized completed ad views.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that ad recognition did not vary in a dose-response manner by randomized exposure levels when participants were able to skip ads but ad recognition was sensitive to non-randomized completed ad views. 42 Although Romberg utilized a digital environment that mimicked real-world online browsing, the research occurred in a lab setting and required participants to physically attend multiple lab visits over time. 42 This type of lab-based protocol can be costly and slow with respect to recruitment and retention efforts, is constrained to local convenience samples and may have limited generalizability to a browsing experience in a person's natural environment.…”
Section: Introductionmentioning
confidence: 99%